Analysis of Service Quality and Customer Satisfaction on Customer Loyalty - Ihdina Gustina; Dedy Lazuardi; Zulkarnain Siregar (Outline Publisher, 2023)
This study aims to determine the effect of Service Quality on Customer Loyalty at Jhon Electro, to determine the effect of Customer Satisfaction on Customer Loyalty at Jhon Electro, to determine the effect of Service Quality and Customer Satisfaction on Customer Loyalty at Jhon Electro. The research population that will be used in the study are all customers who made purchases at the company during the 2020 period as many as 173 customers. By using the Slovin formula with an error rate of 5%, the total sample size is 121 respondents. The results showed that Service Quality and Customer Satisfaction partially had a positive and significant effect on Jhon Electro's customer loyalty. The results showed that Service Quality and Customer Satisfaction simultaneously had a positive and significant effect on Jhon Electro's customer loyalty. The results of this study are supported by the value of R square (R2) which means that Service Quality and Customer Satisfaction have an influence on Customer Loyalty. While the rest is influenced by other factors that come from outside this research model such as price discounts, advertising, customer behavior, price, location and other variables.